2012
DOI: 10.1093/jos/ffr014
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring the meaning of free relative clauses and plural definite descriptions

Abstract: Plural definite descriptions (e.g. the things on the plate) and free relative clauses (e.g. what is on the plate) have been argued to share the same semantic properties, despite their syntactic differences. Specifically, both have been argued to be non-quantificational expressions referring to the maximal element of a given set (e.g. the set of things on the contextually salient plate). We provide experimental support for this semantic analysis with the first reported simultaneous investigation of children'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 18 publications
2
27
2
Order By: Relevance
“…Several previous studies have shown that children have significant difficulties with exhaustivity, suggesting that this problem alone could account for all of the Katsos and Bishop results (e.g. Caponigro et al 2012, Roeper et al 2007). Children who are simply not sure whether a nonexhaustive response to a question is correct may offer intermediate rewards, and similarly may fail to outright reject statements as false.…”
Section: Relevance Implicaturesmentioning
confidence: 90%
“…Several previous studies have shown that children have significant difficulties with exhaustivity, suggesting that this problem alone could account for all of the Katsos and Bishop results (e.g. Caponigro et al 2012, Roeper et al 2007). Children who are simply not sure whether a nonexhaustive response to a question is correct may offer intermediate rewards, and similarly may fail to outright reject statements as false.…”
Section: Relevance Implicaturesmentioning
confidence: 90%
“…Suppose that while children may reliably encode existence presuppositions of definites, they may still have specific difficulties with maximality, as has been argued by Wexler (2011, see also discussion below of Caponigro et al, 2012). If this is the case, children tested on this act-out task should show equal difficulties with both plural and singular definites.…”
Section: Maximality and Domain Restrictions In Child Languagementioning
confidence: 90%
“…This finding is consistent with the hypothesis that difficulties reside in handling inferences needed for implicit domain restriction, and not with maximality encoding. However, a more recent study (Caponigro et al, 2012) raises worries about Munn et al (2006), suggesting that their data may be understood as reflecting a general bias in the plural conditions toward retrieving all the objects. Caponigro et al correctly observe that inclusion of an indefinite plural control condition in the Munn et al study would enable a demonstration that the response patterns for definite plurals may not have been due to a bias toward ALL responses in plural conditions independent of determiner type.…”
Section: Maximality and Domain Restrictions In Child Languagementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, whereas a TVJT requires the relevant set(s) to be predetermined in order for participants to render a judgment of a corresponding sentence, an act-out task allows for participants to create these sets themselves (cf. Caponigro et al 2012). Children may have formed contrasting sets of 'whole sets' for todos and 'proper subsets' for algunos (de los), perhaps driving by something like mutual exclusivity (Markman & Wachtel 1988) or the principle of contrast (Clark 1987).…”
Section: Monolingual Spanish-speaking Childrenmentioning
confidence: 99%